2014
DOI: 10.1103/physrevlett.113.117203
|View full text |Cite
|
Sign up to set email alerts
|

Correlations after Quantum Quenches in theXXZSpin Chain: Failure of the Generalized Gibbs Ensemble

Abstract: We study the nonequilibrium time evolution of the spin-1/2 anisotropic Heisenberg (XXZ) spin chain, with a choice of dimer product and Néel states as initial states. We investigate numerically various short-ranged spin correlators in the long-time limit and find that they deviate significantly from predictions based on the generalized Gibbs ensemble (GGE) hypotheses. By computing the asymptotic spin correlators within the recently proposed quench-action formalism [Phys. Rev. Lett. 110, 257203 (2013)], however,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
435
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(459 citation statements)
references
References 68 publications
18
435
3
Order By: Relevance
“…The difference is more pronounced for the quench starting from the dimer state, although it remains relatively small. However, in this case it is possible to observe the difference between the two predictions [67], and the numerical simulation confirm indeed that the GGE built is Ref. [55] yields wrong prediction, while the representative state approach correctly reproduce the numerical results.…”
Section: -P4mentioning
confidence: 58%
See 1 more Smart Citation
“…The difference is more pronounced for the quench starting from the dimer state, although it remains relatively small. However, in this case it is possible to observe the difference between the two predictions [67], and the numerical simulation confirm indeed that the GGE built is Ref. [55] yields wrong prediction, while the representative state approach correctly reproduce the numerical results.…”
Section: -P4mentioning
confidence: 58%
“…From these overlaps, the infinite time limit of the evolution has been explicitly calculated for the Neel state in Ref. [65,66] and for the dimer state in [67], again exploiting the representative state approach of Ref. [52].…”
Section: -P4mentioning
confidence: 99%
“…The predictions based on GGE resisted all tests in many models both having a free-particle representation [10,11,[14][15][16][17][18][19][20][21][22][23][24] and being genuinely interacting [25][26][27][28][29], until very recently when it has been found that for the XXZ spin chain, after a quench from the (symmetrized) Néel and dimer states, the obtained stationary values [30][31][32] disagree with the predictions of the GGE built with all the known local charges [33,34] (see also Refs. [35][36][37]).…”
Section: Introductionmentioning
confidence: 99%
“…For integrable systems this issue has long been in the focus of research with many interesting findings (cf., for instance, Refs. [20][21][22][23][24][25][26][27]). Generically, integrable systems with a large number of degrees of freedom turn chaotic for a weak perturbation.…”
Section: Introductionmentioning
confidence: 99%